Gas phase ion chemistry of titanium–oxofullerene with ligated solvents. Issue 4 (12th January 2022) - Roy, Jayoti; Chakraborty, Papri; Paramasivam, Ganesan; Natarajan, Ganapati; Pradeep, Thalappil
Abstract : Gas phase fragmentation events of fullerene-like titanium oxo-cluster anions were investigated in detail. The fragmentation channel of the ions was comparable to the fragmentation of C60 ions with systematic C2 losses which is a consequence of topological similarity. Abstract : We investigated the gas phase fragmentation events of highly symmetric fullerene-like (FN-like) titanium oxo-cluster anions, [H12 Ti42 O60 (OCH3 )42 (HOCH3 )10 (H2 O)2 ] 2− (1 ) and [H7 Ti42 O60 (OCH3 )42 (HOCH3 )10 (H2 O)3 ] 1− (2 ). These oxo-clusters contain a closed cage Ti42 O60 core, protected by a specific number of methoxy, methanol, and water molecules acting as ligands. These dianionic and monoanionic species were generated in the gas phase by electrospray ionization of the H6 [Ti42 (μ 3 -O)60 (O i Pr)42 (OH)12 ] (TOF) cluster in methanol. Collision induced dissociation studies of 1 revealed that upon increasing the collision energy, the protecting ligands were stripped off first, and [Ti41 O58 ] 2− was formed as the first fragment from the Ti42 O60 core. Thereafter, systematic TiO2 losses were observed giving rise to subsequent fragments like [Ti40 O56 ] 2−, [Ti39 O54 ] 2−, [Ti38 O52 ] 2−, etc. Similar fragments were also observed for monoanionic species 2 as well. Systematic 23 TiO2 losses were observed, which were followed by complete shattering of the cage. We also carried out computational studies using density functional theory (DFT) to investigate the structures and fragmentation mechanism. The fragmentation of TOF was comparable to the fragmentation of C60 ions, where systematic C2 losses were observed. We believe that this is a consequence of topological similarity. The present study provides valuable insights into the structural constitution of TOF clusters and stability of the parent as well as the resulting cage-fragments in the gas phase.